2020
DOI: 10.1039/d0ja00140f
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a modified halo flowing atmospheric pressure afterglow ion source for the analysis of directly injected volatile organic compounds

Abstract: A modified Flowing Atmospheric Pressure Afterglow source with concentric-tube electrodes (modified-hFAPA) is coupled to an Atmospheric Pressure Interface Time of Flight Mass Spectrometer (API-TOFMS) for the analysis of gas samples....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The FAPA source applies the afterglow from a DC helium glow discharge to thermally desorb and ionize samples. In addition, FAPA has several different geometries, including the original pin‐to‐plate configuration (Andrade et al, 2008a), the pin‐to‐capillary configuration (Shelley et al, 2011), the concentric‐electrode configuration (Pfeuffer et al, 2013), and the modified concentric‐electrode configuration (Fandino et al, 2020). The schematic diagram of the original pin‐to‐plate FAPA is shown in Figure 3 (Ⅰ‐a), the anode is a metal plate with a hole, which allows discharge species to flow into the afterglow region.…”
Section: Plasma‐based Amsmentioning
confidence: 99%
“…The FAPA source applies the afterglow from a DC helium glow discharge to thermally desorb and ionize samples. In addition, FAPA has several different geometries, including the original pin‐to‐plate configuration (Andrade et al, 2008a), the pin‐to‐capillary configuration (Shelley et al, 2011), the concentric‐electrode configuration (Pfeuffer et al, 2013), and the modified concentric‐electrode configuration (Fandino et al, 2020). The schematic diagram of the original pin‐to‐plate FAPA is shown in Figure 3 (Ⅰ‐a), the anode is a metal plate with a hole, which allows discharge species to flow into the afterglow region.…”
Section: Plasma‐based Amsmentioning
confidence: 99%
“…Alves et al reported an ion source for liquid samplingatmospheric pressure glow discharge (LS-APGD) to produce ion intensities equal to or higher (>15%) than that of electrospray ionisation for marine-relevant salt-containing organic samples [20]. Fandino et al evaluated a modified halo-shaped flowing atmospheric pressure afterglow (h-FAPA) source for direct analysis of benzene in volatile organic compounds with low matrix effects [21] and Zhang et al designed a reactive-FAPA ionisation source for rapid isomer differentiation by real-time derivatisation of analytes [22]; moreover, Guć et al analysed perfume components in cosmetics using FAPA-MS by directly determining the fragrance components: patchoulol, farnesol, safrole, geraniol, eucalyptol, and R-carvone [23]. These applications implied that the introduction of afterglow into APGD could not only extend the direct analysis of various types of samples [24], but also provide some possibilities for the identification of short-lived intermediates, even in complicated systems.…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, a halo-flowing atmospheric-pressure afterglow ion source (h-FAPA) was used for the determination of VOCs [ 23 ]. This plasma-based ionization source was combined with an atmospheric pressure ionization time-of-flight mass spectrometer (API-TOFMS).…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen and other oxidized species (e.g., pyrylium) were also observed in the mass spectra due to a special interface between the source and API-TOFMS. Since this is a brand new source type, tested only at a rather stable compound, it is currently hard to predict and evaluate the actual fragmentation of different groups of VOCs [ 23 ].…”
Section: Introductionmentioning
confidence: 99%